Genetic and phenotypic relationships between milk production and body weight in Chios sheep and Damascus goats - Mavrogenis, Andreas; Papachristoforou, Christakis (My University, 2000)
Data on 2087 lactations from 737 Chios ewes collected between 1978 and 1989, and 1611 lactations from 486 Damascus goats collected from 1982 to 1998 at the experimental station of the Agricultural Research Institute were utilized. The ewes were the progeny of 101 sires (mean sire family size 7.3) and the goats of 101 sires (mean sire family size 4.8). A mixed linear model that accounted for the year and season of lambing/kidding and parity of ewes or goats (fixed effects) and sires within years (random effects) was used. Phenotypic and genetic variance and covariance estimates were obtained from paternal halp sib correlations. The study was conducted to investigate genetic and phenotypic relationships between milk production (90-day and total milk) and live weight at mating. Year effects were significant (P<0.01) for all traits studied, while season of parturition significantly affected (P<0.01) only milk production (part and total). Parity had a significant quadratic effect (P<0.01) on all traits examined; the highest response in milk production was reached in the third parity and the highest body weight at mating in the fifth parity. Heritability estimates for 90-day (0.44±0.08 and 0.45±0.11) and total milk yield (0.54±0.09 and 0.49±0.11) for sheep and goats, respectively, were high, indicating that genetic progress from direct selection on either trait would be effective. Heritability of body weight at mating, unadjusted or adjusted to mature equivalent, was high in both species (sheep: 0.79±0.09 and 0.76±0.09, respectively; goats: 0.79±0.11 and 0.80±0.11, respectively). Genetic and phenotypic correlations between part and total lactation yield were both high and positive, justifying selection on early measures of milk production. The genetic associations between production traits and body weight at mating were very low in both species. It was positive in sheep and negative in goats, but no or extremely small correlated responses could be expected in body weight from selection on milk production. Increased body size, when expressed, should be the consequence of better feeding and improved management practices during periods of stress.
Keywords: Milk yield; Mating weight; Sheep; Goat; Relationships; Genetics